The Use of Advertisements and Adbusters in the Course of Business English - Mkhitaryan, Karine (Armenian Folia Anglistika, 2010)
The use of ads and adbusters is a most effective tool in the Business English teaching since it supposes the ability to analyze linguistic and inter-cultural situations which is a necessary precondition for creating ads and adbusters in the given language. It is noteworthy, that the efficiency of a foreign language teaching is first and foremost ensured in case inter-disciplinary relations have been considered, i.e. the ones that exist between the given foreign language and the professional field the student is engaged in. Future specialists of business should be competent in linguostylistic and psychological peculiarities of ads and adbusters. From the methodological perspective they should also be able to create ads, adbusters and resumes using various communicative methods and forms.